2018
DOI: 10.15446/abc.v23n1.63513
|View full text |Cite
|
Sign up to set email alerts
|

Response to in vitro salt stress in sugarcane is conditioned by concentration and condition of exposure to NaCl

Abstract: Salinity is one of the major environmental stress factors that affect crop productivity, as well as interfering with plant growth and development, resulting in reduced production quality. Given this, we highlight the importance of research in response to plants subjected to salt stress in order to assess the physiological and biochemical behavior of genotypes, with the objective of selecting the more tolerant. One way to ensure the uniformity of the response of the plants is through in vitro cultivation, which… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(4 citation statements)
references
References 50 publications
0
4
0
Order By: Relevance
“…Plants use several strategies to detoxify the cell from ROS [53], including the synthesis of low molecular weight compounds and antioxidant enzymes [54], such as catalase, which is considered one of the most important enzymes for the intracellular regulation of peroxide levels under abiotic stresses [55]. At the initial times, the highest specific activity of catalase (CAT) was verified, being around 40% higher in the VuWRKY21 lines at 2 h and, on average, 140% higher at 1 h VuWRKY87 transformed lines.…”
Section: Discussionmentioning
confidence: 99%
“…Plants use several strategies to detoxify the cell from ROS [53], including the synthesis of low molecular weight compounds and antioxidant enzymes [54], such as catalase, which is considered one of the most important enzymes for the intracellular regulation of peroxide levels under abiotic stresses [55]. At the initial times, the highest specific activity of catalase (CAT) was verified, being around 40% higher in the VuWRKY21 lines at 2 h and, on average, 140% higher at 1 h VuWRKY87 transformed lines.…”
Section: Discussionmentioning
confidence: 99%
“…Under saline conditions, plants accumulated Na + at the expense of K + and an optimal Na + /K + ratio is essential for maintaining the enzymatic reactions in the cytoplasm [39]. Since higher Na + /K + indicates excess accumulation of Na + which interfere with the energy utilization pattern that plants exploit to acquire water from the soil, osmotic adjustments might have resulted in reduced plant growth and yield [40][41][42][43]. Among different studied genotypes, Co 0238, Co 05011, Co 0118 and Co 06034 maintained low Na + /K + in all the studied plant parts, due to lower sodium absorption, retaining higher membrane integrity, higher osmolytes and preferential higher K + uptake.…”
Section: Effect Of Salinity On Ion Dynamicsmentioning
confidence: 99%
“…Gandonou et al (2005) studying varieties of sugarcane under conditions of in vitro saline stress, observed that both the sensitive variety CP65-357 and the resistant variety NCo310 behaved similarly, accumulating greater amounts of proline in the more severe saline treatments (102 mM). Granja et al (2018) evaluating the response of two commercial varieties of sugarcane (RB931011 and RB872552), exposed to in vitro salt stress by NaCl (56 mM and 112 mM), concluded that the proline content increased only in plants submitted to treatment with 112mM of NaCl, granting to the sugarcane varieties a greater protection against salt stress. These results reinforce the results found in the present study, in relation to the proline increase in plants submitted to increasing levels of NaCl.…”
Section: Effect Of Salinity On Proline Contentmentioning
confidence: 99%